Staying with the Trouble with Wilderness: Reworking Nature and Culture in the Plantationocene - Johnson, Jordan (Journal of Posthumanism, 2022)
This essay analyzes the use of fire on Upland Island Wilderness Area (UIW) to examine how postindustrial wilderness sites rework operative notions of nature, wildness, and preservation within U.S. environmental thinking and politics. Postindustrial wilderness areas complicate conceptualizations of nature as pristine, unspoiled, or even beautiful, challenging us to address biodiversity and ecosystem function in ways that are less centered on human(ist) values. An intensively managed pine plantation prior to wilderness designation, UIW blatantly transgresses liberal humanist boundaries of nature and culture, ecology and industry. I draw on feminist and posthumanist theory to demonstrate how contestations surrounding the use of fire on UIW resituate ethical and epistemic implications of wilderness management, offering a critical counterpoint to the prioritization of pristine nature within U.S. environmental politics and demanding less humanist approaches to the complex forest ecologies of the plantationocene.